2006
DOI: 10.1002/jbm.b.30625
|View full text |Cite
|
Sign up to set email alerts
|

Sterilization of bacterial spores by using supercritical carbon dioxide and hydrogen peroxide

Abstract: It was hypothesized that supercritical carbon dioxide (SC-CO(2)) treatment could serve as an alternative sterilization method at various temperatures (40-105 degrees C), CO(2) pressures (200-680 atm), and treatment times (25 min to 6 h), and with or without the use of a passive additive (distilled water, dH(2)O) or an active additive (hydrogen peroxide, H(2)O(2)). While previous researchers have shown that SC-CO(2) possesses antimicrobial properties, sterilization effectiveness has not been shown at sufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…As a result, a high degree of reduction of viable spores (up to 6.14 log reduction) has been observed, confirming the sporicidal effects of this mixture at low temperatures for spores of other bacilli (Hemmer, Drews, LaBerge andMatthews, 2006, Zhang, Burrows, Matthews, Drews, LaBerge and. This degree of log reduction meets the sterilization requirement set by the FDA.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…As a result, a high degree of reduction of viable spores (up to 6.14 log reduction) has been observed, confirming the sporicidal effects of this mixture at low temperatures for spores of other bacilli (Hemmer, Drews, LaBerge andMatthews, 2006, Zhang, Burrows, Matthews, Drews, LaBerge and. This degree of log reduction meets the sterilization requirement set by the FDA.…”
Section: Discussionsupporting
confidence: 69%
“…However, the high voltage and high hydrostatic pressure could also be damaging. In our earlier publication, it was shown that at mild temperatures (<60°C), with trace level (~200 ppm) of aqueous hydrogen peroxide, spores of B. atrophaeus ATCC 9372, B. pumilus ATCC 27142, and G. stearothermophilus ATCC 7953 can be reduced in number by more than 6-log (Hemmer et al, 2006.…”
Section: Introductionmentioning
confidence: 97%
“…Treatment efficiency can be proved by the release of DPA to the suspension after the alkaline treatment and TEM observations. It has been previously reported that inactivation of G. stearothermophilus at low temperatures (<100 o C) can be achieved using chemicals agents (Mazzola et al, 2003;Rogers et al, 2007), high-pressure carbon dioxide (Watanabe et al, 2003) and supercritical carbon dioxide with added hydrogen peroxide (Hemmer et al, 2007) but the time required to inactivate spores is high. The D-values found in literature for inactivation assays carried out at temperature 100 o C were higher than those obtained in this work (Table S1), except when using high pressure treatments (Patazca et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We deliberately used less rigorous scCO 2 conditions (lower pressure, lower temperature, and shorter times) than previous investigators (7)(8)(9)(10) who also demonstrated spore killing at a log reduction level of 6 so that we might minimize any potentially deleterious effects on drug substance. In our hands, and under the conditions used, B. pumilus proved to be the most resistant of the three microorganisms tested, whereas B. atrophaeus and G. stearothermophilus tended to show less, but equal susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…While a certain degree of success is obtained with scCO 2 against vegetative forms of several common food contaminants, it was not until recently that methods were described to achieve the sterility assurance level (SAL) of 10 against the difficulty to sterilize spore-forming bacteria that is necessary to produce safe injectable drugs. Several laboratories reported that it is possible to achieve a SAL of 10 −6 against dry spores using scCO 2 with added sterilants (7)(8)(9)(10). These laboratories reported successful destruction of spores using scCO 2 at pressures ranging from 10.34 to 30.34 MPa (1,500 to 4,400 psi), temperatures ranging from 34 to 80°C and for exposure times between 30 min and 4 h.…”
Section: Introductionmentioning
confidence: 99%